Dental caries, dental erosion and periodontal disease in children with inflammatory bowel disease - HAZNEDAROĞLU, EDA (My University, 2023)
Background: There is reportedly a higher prevalence of dental caries and periodontal disease in adults with inflammatory bowel disease (IBD) than in healthy adults. Similar data for children are lacking in the literature. We aimed to evaluate the prevalence of dental erosion, dental caries, and periodontal disease in children with IBD. Methods: This was a cross-sectional comparative study. Using the established criteria of the World Health Organization, oral investigations and detailed questionnaires that covered nutritional habits were completed by the same pediatric dentist for 32 patients with IBD, aged 11 to 18 years (15.53 ± 2.00), and 32 healthy controls. Results: The decayed, missing, and filled tooth index showed no significant difference between the groups (p = 0.072). The frequency of consumption of salad, lemon gum, candy and sweetened milk was significantly higher in the control group (p = 0.041, 0.012, 0.001, and 0.001, respectively) than in the IBD group. No dental erosion was observed in the IBD group. Oral mucosal history determined that 20/32 patients with IBD (62.5%) had at least one oral extraintestinal manifestation. Despite no significant differences in plaque scores between the two groups, the gingival evaluation showed a much higher mean value of gingival index scores in the IBD group than in the control group (p = 0.003). Conclusion: Although the number of patients included in the study is small, we can conclude that oral extraintestinal manifestations and periodontal disease are more prevalent in paediatric patients with IBD than in healthy populations.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; gingival index; nutritional habits; oral extraintestinal manifestation; oral health; permanent dentition; oral health; permanent dentition; nutritional habits; oral extraintestinal manifestation; gingival index